The hunting party : a novel - Foley, Lucy, (Novelist) (New York, N.Y. : William Morrow, an imprint of HarperCollinsPublishers, 2019)
A group of thirty-something Oxford friends celebrate New Year's Eve in the Scottish Highlands as a historic blizzard hits, trapping and isolating them, only to discover one of them is a murderer.
Keywords: Blizzards -- Fiction; Blizzards -- Fiction; Highlands (Scotland) -- Fiction; Highlands (Scotland) -- Fiction; Suspense fiction; Suspense fiction; Psychological fiction